2023
DOI: 10.3389/fpls.2023.1144145
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of limestone dust and lead pollution on the ecophysiology of some selected urban tree species

Abstract: Soil and air pollution caused by heavy metals and limestone dust are prevalent in urban environments and they are an alarming threat to the environment and humans. This study was designed to investigate the changes in morphological and physiological traits of three urban tree species seedlings (Bombax ceiba, Conocarpus lancifolius, and Eucalyptus camaldulensis) under the individual as well as synergetic effects of heavy metal lead (Pb) and limestone dust toxicities. The tree species were grown under controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…A study was conducted on the limestone pollution and its effect ecophysiology of some selected urban tree species. It was found that the photosynthetic rates, stomatal conductance, evapotranspiration rates, and transpiration rates of the trees investigated were negatively influenced in response to different levels of limestone dust's applications [18]. A study was undertaken on the limestone industry in the occupied West Bank and its impacts on energy consumption.…”
Section: Review Of Some Previous Studiesmentioning
confidence: 99%
“…A study was conducted on the limestone pollution and its effect ecophysiology of some selected urban tree species. It was found that the photosynthetic rates, stomatal conductance, evapotranspiration rates, and transpiration rates of the trees investigated were negatively influenced in response to different levels of limestone dust's applications [18]. A study was undertaken on the limestone industry in the occupied West Bank and its impacts on energy consumption.…”
Section: Review Of Some Previous Studiesmentioning
confidence: 99%